Community Diagnosis on Health Seeking Behavior and Social Problems in Bhaktapur and Kavrepalanchok Districts of central Nepal - Manandhar, Pratibha; Manandhar, Naresh; Chandyo, Ram Krishna; Joshi, Sunil Kumar (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: The main objectives of this study were to assess the health status, health seeking behaviors and social problems of Bhaktapur and Kavrepalanchok districts and also to learn the research skills and establish relation with community for students. Materials & Methods: This was a cross sectional study conducted by students of second year MBBS for educational purposes of community diagnosis program (CDP) in one week period in nine VDC (village development committee) of Bhaktapur district along with one VDC and one municipality of Kavrepalanchok district. Household were selected based on convenient sampling method for the feasibility of students. Ethical clearance for the study was taken from Institutional Review Committee (IRC) of Kathmandu Medical College. Results: A total of 211and 105 households from Bhaktapur and Kavrepalanchok districts respectively were included in this study . In Bhaktapur district, a slight female predominance 549 (50.42 %) was observed, whereas in Kavrepalanchok district male predominated marginally 270 (51.1%). In Bhaktapur district, 35 (47.9%) were addicted to alcohol and smoking behaviors, whereas in Kavrepalanchok district it was 12 (29.3%). In Bhaktapur and Kavrepalanchok districts, 102 (48. 3%) and 50 (47.61%) households respectively consulted in hospital when became sick. The most prevalent health problem was cardiovascular diseases in both the districts i,e 39 (39%) in Bhaktapur and 14 (37.8%) in Kavrepalanchok district respectively. Conclusion: Community diagnosis program assisted students to identify problems in the community, to raise the health awareness, practicing research skills and establishing relations with the community. The community also benefitted by getting knowledge on improving the health status and social aspects from the students during their door to door visit.